Estudo etnobotânico da planta medicinal barbatimão nas comunidades rios Doce e da Prata, município de Abaetetuba, Pará - SILVA, Marli Maués da (2019)
The popular use of medicinal plants for the treatment and cure of diseases is an ancient practice in humanity and its uses are precisely linked to the miscegenation of cultures, customs and values that are passed on between generations. This study aimed to carry out an ethnobotanical study of the medicinal plant Barbatimão used by the riverine residents of the Rios Doce and Prata communities, municipality of Abaetetuba, Pará. The selection of the collaborators took place through the snowball methodology. Sixty-one participants were included in this research, 58 female and three male, all literate, aged between 33 and 99 years old. It was collected and identified the species Connarus perrottetti, the bark is the most used part of the plant to make teas, bath and bottle, these formulations are indicated for uterus infection, skin wounds, cancer and vaginal discharge, according to the collaborators. They do not cause any undesirable effects and their use may be internal and external. The barbatimão used in herbal medicine of these communities is of great importance to the population, because the ways of preparation and use of these home remedies meet the demands of these residents.